Talquetamab plus daratumumab for the treatment of relapsed or refractory multiple myeloma in the TRIMM-2 study - Chari, Ajai; van de Donk, Niels W. C. J.; Dholaria, Bhagirathbhai; Weisel, Katja; Mateos, María-Victoria; Goldschmidt, Hartmut; Martin, Thomas G.; Morillo, Daniel; Reece, Donna; Rodríguez-Otero, Paula; Bhutani, Manisha; D’Souza, Anita; et al. (Blood, 2025)
Talquetamab, a G protein-coupled receptor class C group 5 member D-targeting bispecific antibody for relapsed/refractory multiple myeloma (R/R MM), plus daratumumab, may lead to deeper and more durable responses than either therapy alone. In the phase 1b TRIMM-2 study, patients with R/R MM (at least 3 previous lines of therapy or double refractory to a proteasome inhibitor and an immunomodulatory drug) received subcutaneous talquetamab 0.4 mg/kg weekly (QW; “QW cohort”) or 0.8 mg/kg every other week (Q2W cohort) plus daratumumab 1800 mg per the approved schedule. The primary end point was safety. Secondary end points included overall response and duration of response. Progression-free survival was an exploratory end point. Sixty-five patients (median 5 previous lines of therapy; 61.5% triple-class refractory; 24.6% bispecific antibody exposed) received talquetamab plus daratumumab (QW, n = 14; Q2W, n = 51; median follow-up of 18.6 months). Most common adverse events were oral events, skin events, cytokine release syndrome, and infections. Grade 3 or 4 events occurred in 81.5%. Two patients had dose-limiting toxicities, both in the Q2W cohort (grade 3 stomatitis/oral mucositis, and grade 3 maculopapular rash). Responses occurred in 71.4% (QW cohort) and 82.4% (Q2W cohort) of patients. Median progression-free survival was 23.3 and 21.2 months, respectively, in each cohort. Pharmacodynamic results suggest the immunomodulatory action of daratumumab contributes to a conducive environment for talquetamab by reducing immunosuppressive cells. Talquetamab plus daratumumab demonstrated promising efficacy outcomes in patients with heavily pretreated disease, with a safety profile consistent with each agent as monotherapy. This trial was registered at www.clinicaltrials.gov as #NCT04108195.
Gesehen am 20.02.2026